Penyajian Data - Nurhaswinda, Nurhaswinda; Maulina, Syalsa Riski Maulina; Azzahra, Azzahra; Jannah, Fitri; Jannah, Nurwidiatul; Fadila, Nurul Aini; Harza, Zalfi Juni; Hariza Putra, Naufal (LANCAH: Jurnal Inovasi dan Tren, 2025)
presentation in statistics, as well as various forms of presentation that can facilitate data analysis and interpretation. The method employed in this writing is a literature review, which involves analyzing theories and previous research related to data presentation. The findings of this review indicate that effective data presentation not only enhances the understanding of information but also aids in making accurate decisions. There are various forms of data presentation, such as tables, graphs, and diagrams, each with its own advantages in conveying information. In conclusion, systematic and clear data presentation is essential to ensure that information is well understood and supports the desired analytical objectives.